2010
DOI: 10.1002/cphc.200900849
|View full text |Cite
|
Sign up to set email alerts
|

Ion and pH Sensing with Colloidal Nanoparticles: Influence of Surface Charge on Sensing and Colloidal Properties

Abstract: Ion sensors based on colloidal nanoparticles (NPs), either as actively ion-sensing NPs or as nanoscale carrier systems for organic ion-sensing fluorescent chelators typically require a charged surface in order to be colloidally stable. We demonstrate that this surface charge significantly impacts the ion binding and affects the read-out. Sensor read-out should be thus not determined by the bulk ion concentration, but by the local ion concentration in the nano-environment of the NP surface. We present a conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
143
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(149 citation statements)
references
References 56 publications
(47 reference statements)
3
143
0
Order By: Relevance
“…In this way, ligands on the NP surface introduce higher flexibility in achieving ( pH-independent) colloidal stability, in particular via permanently charged ligands and/or ligands providing steric repulsion. As for ligand-free NPs, besides the charge directly associated with the NP surface (now here in particular to the ligand shell), also ligand-coated NPs comprise a diffusive cloud of charge figure 7a, [55]). Please note that these effects are absolutely non-specific and only depend on charge and valency of the ions.…”
Section: Effects Of Ion-induced Nanoenvironments On the Stability Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, ligands on the NP surface introduce higher flexibility in achieving ( pH-independent) colloidal stability, in particular via permanently charged ligands and/or ligands providing steric repulsion. As for ligand-free NPs, besides the charge directly associated with the NP surface (now here in particular to the ligand shell), also ligand-coated NPs comprise a diffusive cloud of charge figure 7a, [55]). Please note that these effects are absolutely non-specific and only depend on charge and valency of the ions.…”
Section: Effects Of Ion-induced Nanoenvironments On the Stability Andmentioning
confidence: 99%
“…However, in the case the NP surface is saturated with attached spacer molecules, they all will adopt similar geometry and thus lead to defined distances R. Fluorophores can be linked to the end of the spacer molecules [147,148], and by using spacers with different molecular weight the average distance between fluorophores and the NP surface can be tuned [143,149,150]. This principle has been applied to sense local H þ [55,57] and Cl 2 [56] concentrations. According to figures 7 and 8 for negatively charged NPs, higher H þ and lower Cl 2 concentrations were found close to the NP surface when compared with bulk.…”
Section: Effects Of Ion-induced Nanoenvironments On the Stability Andmentioning
confidence: 99%
“…Previous work has already demonstrated that strong ligand-ligand interactions required for NP film stability are attainable not only for alkanethiol-AuNPs [20][21][22]45,46 , but other core materials such as cobalt oxide and iron oxide with oleylamine and oleic acid ligands 21 , as well as DNA-coated NPs 47 . The end result is a potentially powerful route towards engineering a set of desired interactions in which colloidal NPs are functionalized a priori with the desired functionality 48,49 . In short, ligated NPs serve as fully functionalized building blocks for a type of bottomup assembly for the active layer of membranes.…”
Section: Article Nature Communications | Doi: 101038/ncomms6847mentioning
confidence: 99%
“…In fact, the development of novel methods based on nanoparticles (NPs) for sensing ions has experienced significant growth during the last decade. [1][2][3][4][5][6][7][8] Among ions, heavy metal ions such as lead, cadmium, and mercury have attracted more attention due to their high toxicity and detrimental health effects. [7][8][9][10][11] Exposure to even very low levels of lead, cadmium, and mercury ions is known to cause cardiovascular diseases, cancer mortality, damage to liver, kidneys, and central nervous system, neurological, reproductive and developmental disorders, which are more serious problems for children particularly.…”
Section: Introductionmentioning
confidence: 99%
“…In this area, the coupling of ion-sensitive fluorophores to NPs has been of special interest because they can be detected easily using fluorescence microscopy, therefore, allowing the monitoring of dissolved ion concentrations in living cells and organisms. [1][2][3][4][5] Quantum dots (QDs) have been used in spectroscopic detection of metal ions since 2002, 26 and a wide range of ions have been investigated-for both transition metals 27 and heavy metals. 28, 29 However, we focus here on the development of QDbased sensors for the most relevant toxic heavy metal ions, Cd 2þ , Pb 2þ , and Hg 2þ .…”
Section: Introductionmentioning
confidence: 99%